Remote ischemic post-conditioning protects against myocardial ischemia/reperfusion injury by inhibiting the Rho-kinase signaling pathway - Min, Feng (Exp Ther Med, 2020)
The aim of the present study was to observe the effect of Rho-kinase on remote ischemic post-conditioning (RIPostC) and explore the underlying mechanisms. Male Sprague Dawley rats (n=32) were randomly distributed into four groups: Sham group, ischemia/reperfusion (I/R) group, RIPostC group and I/R with fasudil group (I/R+Fas). Infarction size was detected by triphenyltetrazolium chloride staining. The levels of creatine kinase (CK), lactate dehydrogenase (LDH), superoxide dismutase (SOD), malondialdehyde (MDA) and cardiac troponin I (cTnI) were measured using an ultraviolet spectrophotometer. The mRNA expression levels of Rho-associated coiled-coil containing protein kinase (ROCK)-1 and ROCK2, B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X protein (Bax) were detected via reverse transcription-PCR. The protein expression levels of phosphorylated-myosin phosphatase target subunit (p-MYPT1) and phosphorylated-myosin light chain (p-MLC) were assessed by western blotting. The results demonstrated that RIPostC could decrease the infarct size, the levels of CK, LDH, cTnI and MDA and increase the activity of SOD compared with the I/R group. In addition, the mRNA expression of ROCK1 and ROCK2 was downregulated, the protein expression of p-MYPT1 and p-MLC was decreased, and the ratio of Bcl-2/Bax was elevated in the RIPostC groups compared with the I/R group. Notably, the aforementioned index in I/R with Fas group was similar to the RIPostC group and no significant difference was observed between RIPostC and I/R+Fas. These results revealed that RIPostC could attenuate I/R injury and the underlying mechanisms might be associated with a reduction in myocardial apoptosis and the suppression of the Rho-kinase signaling pathway.